Regulation of Osteosarcoma Cell Proliferation, Migration, and Invasion by miR-143 and miR-199a Through COX-2 Targeting - Huang Bixin; Zheng Yuling; Mai Ying; Chen Jinming; Zhongqi Zhang (SAGE Publishing, 2024)
Objective To investigate the biological role of miR-143 and miR-199a in mediating the progression of osteosarcoma (OS) by targeting cyclooxygenase (COX-2). Introduction COX-2 plays a crucial role in the development and progression of OS. However, the specific regulatory mechanisms of COX-2 in OS are still not well understood. Methods The expression levels of COX-2, miR-143 and miR-199a in OS tissues were detected using immunohistochemistry, qPCR, or western blot assays. The targeting relationship between miRNAs and COX-2 was determined. The effect of miRNA and COX-2 on OS cells was evaluated in vitro and in vivo. Results COX-2 expression was upregulated while miR-143 and miR-199a were downregulated in OS tissues. miR-143 and miR-199a suppressed the proliferation, migration, and invasion of OS cells. The dual-luciferase reporter gene assay showed that COX-2 was a direct target of miR-143 and miR-199a. Genetic knockdown of COX-2 significantly suppressed cell proliferation, induced apoptosis, and inhibited migration and invasion of OS cells. The expression levels of COX-2 and PGE2 were decreased after the overexpression of miR-143 and miR-199a. Additionally, COX-2 silencing inhibited the tumorigenesis of OS and the synthesis of PGE2 in vivo. Conclusions miR-143 and miR-199a/COX-2 axis modulates the proliferation, invasion, and migration in osteosarcoma.